Números primos. - Padilha, José Cleiton Rodrigues (2013)
The purpose of this work is to present a special category of integers: Prime numbers. It will be presented a historical retrospective, quoting the most important and interesting results achieved by great mathematicians over the years. Then, most of these results will be formally announced with propositions or theorems and their respective demonstrations, starting with the basic properties of divisibility and cul- minating in some primality tests.